PELAYANAN ADMINISTRASI KEPEGAWAIAN - Saleh, Sirajuddin (Pascasarjana Universitas Negeri Makassar, 2016)
Personnel administration services is one type of administrative services at the Faculty of education is still often get the spotlight from the employee served. Various deficiencies or weaknesses in providing administrative services personnel need to be evaluated in order to get a completion, so that service personnel in the future much simpler to keep referring to the basic essence that employment rights can be obtained when the obligations have been met by the civil servants concerned. Therefore the speed, accuracy and thoroughness in providing staffing services will provide more value when the settlement process can be done on time and on target. The results showed that: (i) Service personnel administration at the Faculty of Education, State University of Makassar as a whole has not been optimal. This is due to the absence of a set of service standards as a guide in providing administrative services personnel. (ii) Factors that support the implementation of administrative services officers are sufficient numbers of staff there still exists some employees who have the passion and motivation, and reward / compensation is adequate. While the factors that hinder the work is the absence of procedures, the ability of officers who are still limited, inadequate support facilities as well as the discipline of some employees are still low.